Intraoperative Corticosteroid Injections in Migraine Surgery: Efficacy in Preventing Refractory Symptoms. Issue 2 (February 2015) - Lineberry, Kyle; Lee, Michelle; Monson, Andrea; Guyuron, Bahman
Abstract : Background: A subset of patients have been noted to have refractory migraine symptoms in site IV (occipital triggers) following primary surgery. It was postulated that the cause of refractory migraine symptoms is new scar tissue formation causing irritation of the greater occipital nerve. The goal of this study was to determine whether intraoperative corticosteroid injections have the potential to prevent these refractory symptoms. Methods: A retrospective review of all patients operated on by the senior author (B.G.) from 2000 to 2010 was undertaken. All patients who had site IV decompression and at least 1 year of follow-up were included. Patients were divided into two groups, those who had corticosteroids injected and those who did not. Data analyzed included demographics and preoperative and postoperative migraine headache symptoms review based on the migraine headache questionnaire. Results: A total of 476 patients were included in the study. There were 282 patients in the corticosteroid group and 194 in the no-corticosteroid group. A significant reduction was found in the frequency of migraine headaches (−9.8 versus −8.0; p = 0.03) and the migraine headache index (−92.9 versus −65.2; p = 0.0065). There was no significant reduction in migraine headache duration (−0.50 versus −0.70; p = 0.10) or severity (−3.50 versus −3.80; p = 0.38). Conclusions: Intraoperative injection of corticosteroids during site IV migraine surgery may reduce migraine frequency and migraine headache index postoperatively. Corticosteroid injection in migraine site IV surgery is an effective adjunctive measure in reducing the migraine headache index. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.